2018
DOI: 10.1111/jonm.12716
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of working in rural hospitals: An integrative review

Abstract: This review highlights some key issues impacting nurses' working in rural hospitals. This understanding can be used by nurse managers to inform strategies for recruitment and retention of nurses in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
(129 reference statements)
3
31
0
1
Order By: Relevance
“…The present study's ndings further indicated that the odds ratio of nurses within 1 year work experience were about four fold as likely to indicate intention to stay in their current job as compared to their counterparts with 5~10 years of experience in nursing (Table 4). Such ndings are also in accordance with previously reported studies in the literature [24]. Sociocultural factors associated with the role of experienced workers in society may also play a role in enhancing the job retention of nurses [25].…”
Section: Discussionsupporting
confidence: 93%
“…The present study's ndings further indicated that the odds ratio of nurses within 1 year work experience were about four fold as likely to indicate intention to stay in their current job as compared to their counterparts with 5~10 years of experience in nursing (Table 4). Such ndings are also in accordance with previously reported studies in the literature [24]. Sociocultural factors associated with the role of experienced workers in society may also play a role in enhancing the job retention of nurses [25].…”
Section: Discussionsupporting
confidence: 93%
“…One of the main incentives used to recruit and retain health workers in remote areas is by offering continued professional development (CPD), sometimes virtually [21,73,105]. CPD is the second reason why recruits choose rural programs in Australia, after financial incentives [106].…”
Section: Non-financial Incentivesmentioning
confidence: 99%
“…The aim of having support systems and group practices is to reduce burdens and isolation. It is one of the highest predictors of job satisfaction and retention in rural areas [105]. Professional support was also one of the main enablers of considering rural practice for dental students in Canada [107].…”
Section: Non-financial Incentivesmentioning
confidence: 99%
“…26 Further to this, nurses asked to work outside their conscience are at risk of burnout and injury through the psychological and negative physical health effects of moral distress. 2 Given the staffing issues in this scenario, consistent with the experience of many rural and remote care settings, 27 risking the health of a nurse through moral injury in an already staffing-challenged unit or area could compromise the care of many other residents.…”
Section: Data and Moral Claimsmentioning
confidence: 97%